Odpowiedź:
Zad 12
a = -4
b= -8
a + b
-4 + (-8) = -12
a*b
-4 * (-8) = 32
a-b
-4 - (-8) = -4 + 8 = 4
a : (-b)
-4 : (-(-8)) = -4 : 8 = -0,5
b - a
-8 - (-4) = -8 + 4 = -4
(-a) * b
(-(4)) * (-8) = 4 * (-8) = -32
a + (-b)
-4 + (-(-8) = -4 + 8 = 4
(-b) : (-a)
-(-8) : (-(-4)) = 2
Zad 13
a) (-2 + 9) * (-3) = -21
b) (-4 - 8) * (7 - 11) = -16
c) -4 * 5 - 7 * (-2) = -6
d) 3 - (-5)/ -4 = 2
e) (-16 - 8) : (-4 + 10) = -4
f) (-2) * (5 - 9) - (-7 + 3) = -2
g) -7 + 8 : (-2) - 3 * (-5) = -19
h) (14 - 19) - (27 - (-3))/ 20 - 25 = 7
Szczegółowe wyjaśnienie:
* to znak mnożenia
/ to kreska ułamkowa